Guess who's there: Employment protection legislation and the degree of substitutability between labour contracts - Daniela Sonedda (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
Employment protection legislation may affect the degree of substitutability among different types of labour contracts by changing the individuals sorting into jobs and firms screening in and out jobs. Using administrative data, we document this substitutability in the context of a labour market reform that changed the informative content of individual dismissals and provided incentives to training contracts in Italy in 2012. We present and simulate a model that shows that individual's and firm's behaviour have important implications for the impact of policies that lower firing costs. A more flexible employment protection legislation regime combined with incentives to training contracts reduces inefficiencies of job sorting and screening due to asymmetric information.
Keywords: J24; J63; J68; 330; Human Capital; Employment Protection Legislation; Asymmetric-information